Electronic surveillance, privacy and national security: concepts, analysis - in a nutshell - Khan, Md. Zubair Kasem; Zulhuda, Sonny (The Malaysian Current Law Journal Sdn Bhd, 2014)
With the profound proliferation of sophisticated technologies throughout the globe, the efficacy of electronic surveillance has been intensifying ostentatiously over the last two decades. The ratiocination behind conducting e-surveillance is manifested from the point of vexation of national security, however, such event must be carried out by showing probity and esteem for inherent privacy right of every individual. The purpose of the author is to delineate the very abstraction of the slippery terms: privacy and electronic surveillance in divergent points of views and measure the implication of these on the ground of national security.